Disorder-Induced Phase Transitions in the Transmission of Dielectric Metasurfaces - Rahimzadegan, Aso; Arslan, D.; Suryadharma, R. N. S.; Fasold, S.; Falkner, M.; Pertsch, Thomas; Staude, I.; Rockstuhl, Carsten (Physical Review Letters, 2019)
Light interaction with disordered materials is both complex and fascinating at the same time. Here, we reveal disorder-induced phase transitions in a dielectric Huygens' metasurface made from silicon nanocylinders that simultaneously support an electric and magnetic dipole resonance. Depending on the degree of positional disorder and the spectral detuning of the two resonances, the phase angle of the transmission coefficient exhibits a clear phase transition from normal to anomalous dispersion. Combined with the considerations of whether the resonances of spectrally detuned particles appear as separated or overlapping, we distinguish four different phase states. We study this phenomenon analytically by employing dipole particles and disclose the entire phase diagram, support our insights with full-wave simulations of actual structures, and corroborate the findings with experimental results. Unveiling this phenomenon is a milestone simultaneously in the growing fields of metamaterial-inspired silicon nanophotonics, photonics in disordered media, and the fundamental physics of phase transitions.
CRIS-Team Scopus Importer:2023-04-20